Analysis Of Factors Influencing The Conversion Of Rubber Land To Oil Palm In Tebo Regency - Indah Ayu -Pangesti; Saidin Nainggolan; Rozaina Ningsih (Politeknik Pertanian Negeri Samarinda, 2025)
The decreasing trend of rubber land area and increasing oil palm land area in Rimbo Ilir District, Tebo Regency, from 2019 to 2023 indicates a conversion of rubber land to oil palm land. This study aims to: determine the description of the conversion of rubber land to oil palm in Rimbo Ilir District, Tebo Regency, analyze the factors that influence the conversion of rubber land to oil palm. This study was conducted in three villages: Sari Mulya Village, Karang Dadi Village, and Sepakat Bersatu Village, with a sample of 66 farmers. The sampling method was carried out in two stages: simple random sampling and proportional stratified random sampling. The data analysis method used in this study was binary logistic regression analysis. The results of the study indicate that The conversion of rubber land to oil palm in Rimbo Ilir District has occurred since 2015, with an average area of ​​land converted of 4 hectares. The land conversion process includes cutting down rubber trees, determining planting distances, plant maintenance, and harvesting when the oil palm is at least 4 years old. Farmers' decisions to convert rubber land to oil palm are significantly influenced by seven variables, namely: number of family members, land area, farming experience, technical conditions, economic motives, other sources of income, and farmer ethnicity. Of the seven variables, six variables have a positive effect, while the number of family members has a negative effect on farmers' decisions to convert rubber land to oil palm.